Platelet-rich fibrin to manage different periodontal defects combine with Flap surgery and other uses in dentistry. A descriptive review - Md Ashif Iqbal; Marjana Hossain Mim; Nayna Binte Shahabuddin (Update Dental College, 2021)
In these days, periodontal diseases are very much common in Asian subcontinent especially in Bangladesh, due to some relevant factors that is more prevalent in this country. Most of the time patient neglect their condition and ultimately loss their teeth. Even after doing phase 1 therapy that is scaling, polishing with antimicrobial agents, it could not heal the periodontal condition with advanced bone destruction or clinical attachment loss. Therefore, after proper oral hygiene maintenance therapy, different flap surgery should consider. . In recent study, it is found that platelet rich fibrin (PRF) PREPARED From the patient's Own blood and then placement within defect could enhance the early healing procedure. This PRF membrane is also used in a variety of discipline in dentistry, including regenerative surgery. This PRF membrane is now used in a variety of disciplines in dentistry, including regenerative surgery and enhancing early healing. The goal of this study is to critically analyze and appraise the currently available research with an emphasis on the use of PRF in regenerative periodontal surgery.  An electronic search was conducted (PubMed/MEDLINE, Google Scholar, BanglaJOL, Cochrane library). Various combinations of the following keywords were used: 'prf', 'prf membrane', 'periodontal regenerative surgery', 'prf in dentistry', 'systemic diseases and periodontitis', 'drawback of prf', 'platelet-derived growth factors', 'prf in oms', 'prf in orthodontics'. Articles were searched until August 2021 All of these studies reveal that the PRF membrane enhances the healing of various defects in a variety of periodontal diseases and in several fields of dentistry. Studies are going on pulp regeneration and socket healing after extraction with PRF in dentistry. More emphasis should have to give to the prevention of periodontal diseases as well as more concern should have to give on PRF with flap surgery to enhance healing and improve the social health of the general population by preventing tooth loss and for different research purposes on PRF in different other fields of dentistry in Bangladesh. Update Dent. Coll. j: 2021; 11(2): 43-51